1989
DOI: 10.1007/bf03005353
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthesia and Rett syndrome: a case report

Abstract: Rett syndrome is a neurological disorder of females characterized by dementia, autism, movement disorders and an abnormality of respiratory control. A 14-year-old girl with Rett Syndrome underwent spinal fusion surgery under general anaesthesia. No exacerbation of the respiratory control defect with surgery and anaesthesia was observed. Hypothermia, ongoing blood loss and a normal anion gap acidosis were encountered, but were not attributable to features of this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 9 publications
0
10
0
1
Order By: Relevance
“…Many experts believe that the brainstem function of patients with Rett syndrome is immature and might be a factor in causing unexpected sudden death in some patients. 25,26,[28][29][30] This feature might have played a role in our patients with prolonged apnea. This is the largest study to date documenting the effects of deep sedation in patients with Rett syndrome.…”
Section: Discussionmentioning
confidence: 89%
“…Many experts believe that the brainstem function of patients with Rett syndrome is immature and might be a factor in causing unexpected sudden death in some patients. 25,26,[28][29][30] This feature might have played a role in our patients with prolonged apnea. This is the largest study to date documenting the effects of deep sedation in patients with Rett syndrome.…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, we determined that the timing of her operation was appropriate. Patients with Rett syndrome reportedly have individual variability in sensitivity to anesthetic agents and muscle relaxants [9,10]. Therefore, it is strongly recommended that the BIS monitor and muscle relaxation monitor be used to avoid both insufficient anesthesia and delayed awaking.…”
Section: Discussionmentioning
confidence: 99%
“…These children may be at risk of recurrent aspiration and impaired respiratory function due to muscle weakness and thoracic deformity. In addition, abnormal patterns of respiration are commonly seen 10 . Cirignotta et al (8) have suggested that the frequent desaturations may cause permanent hypoxic damage and contribute to the progressive cerebral deterioration.…”
Section: Consentmentioning
confidence: 99%
“…Rett syndrome (RS) is a progressive developmental syndrome that occurs at the rate of 10,000-23,000 throughout the world and courses with autism, dementia, ataxia and loss of manual dexterity in girls 1 . It is the second leading cause of mental retardation among girls following Down syndrome 2 .…”
Section: Introductionmentioning
confidence: 99%